Long‐term dosing patterns of enteric‐coated mycophenolate sodium or mycophenolate mofetil with tacrolimus after renal transplantation. (22nd July 2014) - Langone, Anthony; Shihab, Fuad; Pankewycz, Oleh; Doria, Cataldo; Wiland, Anne; McCague, Kevin; Chan, Laurence
Abstract MORE was a four‐yr, prospective, observational study at 40 transplant centers in the US. Data were analyzed to evaluate changes in mycophenolic acid (MPA) dosing over time in 904 de novo kidney transplant recipients receiving enteric‐coated mycophenolate sodium (EC‐MPS, n = 616) or mycophenolate mofetil (MMF, n = 288) with tacrolimus. Induction therapy and steroid treatment were similar in the two subpopulations. The proportion of patients receiving the maximal recommended MPA dose was 80.5%, 43.9%, 39.2%, 34.6%, and 30.1% at baseline and years 1, 2, 3, and 4, respectively. More patients received the maximal recommended MPA dose with EC‐MPS vs. MMF at month 1 (79.2% vs. 71.7%, p = 0.016), month 3 (68.5% vs. 56.9%, p = 0.001), and month 6 (52.9% vs. 44.0%, p = 0.028). Multivariate analysis showed the risk of biopsy‐proven acute rejection, graft loss or death to be similar for EC‐MPS vs. MMF. Estimated glomerular filtration rate (GFR) was similar with EC‐MPS vs. MMF at all time points. There were no significant differences in any category of adverse event between the EC‐MPS and MMF cohorts during follow‐up, including gastrointestinal events. In conclusion, MPA dose was maintained more effectively in the first six months after kidney transplantation using EC‐MPS vs. MMF, without an increase in adverse events.